2014
DOI: 10.1007/s00256-014-2086-0
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: MRI features of the anterolateral ligament of the knee

Abstract: The original version of this article unfortunately contained typing errors. The words 'thickness' and 'width' were switched. Find bellow the corrections:Page 1, Results section of Abstract A completely visible ligament had a mean length of 33.2 mm, thickness of 5.6 mm, and width of 1.9 mm. Where it should have read as: A completely visible ligament had a mean length of 33.2 mm, width of 5.6 mm, and thickness of 1.9 mm. Page 4, First paragraph of Reading parameters and statistical analyses of Results A complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Helito et al 12 showed that the ALL is fully visualized in 71.7% of the MRIs. In turn, Taneja et al 13 have identified the full ALL view in 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Helito et al 12 showed that the ALL is fully visualized in 71.7% of the MRIs. In turn, Taneja et al 13 have identified the full ALL view in 11%.…”
Section: Discussionmentioning
confidence: 99%